2011
DOI: 10.1248/cpb.59.1263
|View full text |Cite
|
Sign up to set email alerts
|

Drug Penetration of the Posterior Eye Tissues after Topical Instillation: In Vivo and in Silico Simulation

Abstract: The purpose of this study was to analyze drug pharmacokinetics in the posterior eye tissues after topical instillation. For the in vivo study, the concentrations of ofloxacin in rabbit ocular tissues were analyzed by high performance liquid chromatography at 1, 2, and 3 h after instillation. For the in silico simulation, the concentration distribution of ofloxacin in the eye was calculated by the ocular pharmacokinetic model based on the diffusion/partition model. The simulated profiles were then compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…More recently, CFD models have been built for the complete eye enabling simultaneous evaluation of drug kinetics in the anterior and posterior segments of the eye after IVT and topical application (11,(20)(21)(22)(23)(24)(25). The most comprehensive study on IVT administration was published by Missel (11) who built anatomically accurate models for human, rabbit and monkey eyes based on MRI, and validated the rabbit model using published in vivo data on six compounds with a wide range of molecular weights (0.3-157 kDa).…”
mentioning
confidence: 99%
“…More recently, CFD models have been built for the complete eye enabling simultaneous evaluation of drug kinetics in the anterior and posterior segments of the eye after IVT and topical application (11,(20)(21)(22)(23)(24)(25). The most comprehensive study on IVT administration was published by Missel (11) who built anatomically accurate models for human, rabbit and monkey eyes based on MRI, and validated the rabbit model using published in vivo data on six compounds with a wide range of molecular weights (0.3-157 kDa).…”
mentioning
confidence: 99%
“…The proposed mechanism of HP β CD combined with NLC in the enhanced lutein accumulation includes the following possibility. In the process of corneal permeation, the drug should be released from the vehicles followed by partition or absorption into the cornea [35]. The diffusion rate of drugs from the vehicle is essential for the corneal accumulation of drugs [36].…”
Section: Resultsmentioning
confidence: 99%
“…For example, Tojo (2004) reported a PK model for ocular drug delivery. In silico drug penetration was reported in the posterior eye tissues after topical instillation in rabbits (Shikamura et al, 2011). In addition, Ueda et al (2010) reported an ocular diffusion model of antimicrobial drugs in normal and diseased eyes.…”
Section: In Silico Prediction Of Ocular Exposure and Risk Assessment mentioning
confidence: 99%